Initial Trials With Susceptibility-Based and Empiric Anti-H. pylori Therapies in Mongolia - Byambajav, Tsogt-Ochir; Bira, Namdag; Choijamts, Gotov; Davaadorj, Duger; Gantuya, Boldbaatar; Sarantuya, Tserenchimed; Sarantuya, Gidaagaya; Enkhtsetseg, Altangerel; Erdenetsogt, Dungubat; Battulga, Adiyasuren; Tserentogtokh, Tegshee; Matsuhisa, Takeshi; et al. (Frontiers in Pharmacology, 2019)
Background: Mongolia has a high prevalence of Helicobacter pylori infection and gastric cancer. We conducted a prospective, randomized, single-blind study to evaluate the efficacy of common regimens in Mongolia and to obtain specimens for susceptibility testing. Methods: Empiric treatments: 270 patients with confirmed H. pylori-infection were randomized to receive 10 days clarithromycin-triple therapy (n = 90); modified bismuth quadruple therapy (n = 90), or sequential therapy (n = 90). A second group of 46 patients received susceptibility-based clarithromycin-triple therapy. H. pylori was cultured from 131 patients and susceptibility testing was performed. H. pylori eradication was confirmed by stool antigen 4 weeks after the therapy Results: Intention-to-treat analysis cure rates were 71.1% (95% CI = 61.7% to 80.5%) for clarithromycin-triple therapy, 87.8% (95% CI = 81% to 94.6%) for modified bismuth quadruple therapy, 67.8% (95% CI = 58.1% to 77.5%) for sequential therapy vs. 89.1% (95% CI = 86% to 98.2%) for susceptibility based clarithromycin-triple therapy. Per-protocol analysis results for these therapies were 72.7% (63.4% to 82%), 89.8% (83.5% to 96.1%), 68.5% (58.8% to 78.2%) and 97.6% (89.5% to 99.8%), respectively. Among 131 cultured H. pylori resistance rates to amoxicillin, clarithromycin, and metronidazole were 8.4%, 37.4%, and 74%, respectively. Conclusion: In Mongolia the prevalence of H. pylori resistance is high requiring bismuth quadruple therapy or susceptibility-based therapy to obtain acceptable cure rates.